Oxidation of core–shell MoO2–MoS2 nanoflakes in different O2 ambience. (15th March 2017) - Kumar, Prabhat; Singh, Megha; Reddy, G B
Abstract: Oxidation of MoO2 /MoS2 core–shell nanoflakes (NFs) has been investigated in different oxidation ambients i.e. oxygen (O2 ) gas and its plasma. Core–shell nanoflakes are oxidized at temperatures varying from 150 °C to 450 °C and the effect of oxidation temperature on the structural and morphological changes of nanoflakes are investigated systematically. High-resolution transmission electron microscopy (TEM) images show that shell of nanoflake is oxidized with varying thicknesses and strongly depending upon the temperature and ambience. X-ray diffraction (XRD) and Raman analysis revealed the formation of MoO3 at low temperature (⩽150 °C) in O2 plasma. Whereas, in O2 gas at a relatively higher temperature (⩾350 °C). Scanning electron microscopy (SEM) results show noticeable changes in the morphology as deformation of nanoflakes after oxidation. X-ray photoelectron spectroscopy (XPS) revealed, oxidizing in O2 -plasma led to multiple oxidation states of Mo (4 +, 5 +, and 6 + ) and S (2 −, 6 + ). It is evident that the extent of oxidation of MoS2 shell is higher in plasma due to reactive species of oxygen (O +, O 2 +, O *, etc), as compared to O2 gas.